Analisis Kepribadian Tokoh Utama Wira dalam Novel Cinta 31.000 Kaki Karya Dokter Gia Pratama Kajian Psikologi Sastra - Shinta Noviana Lubis; Gustianingsih Gustianingsih; Bambang Riyanto (Journal on Education, 2024)
A novel is a story or story carried by certain actors with various background roles and stages and a series of stories obtained from the author's imagination so that a story is woven. The novel tells a picture of the character's life as a result of almost the entire journey of life. In the novel there is also a personality that includes all thoughts, feelings and behavior, consciousness and unconsciousness. This study aims to describe the personality structure of the main character in the novel Cinta 31,000 Kaki by Dr. Gia Pratama. The method used in this research is descriptive qualitative method. The data in this study are in the form of quotations taken from the content of the novel Cinta 31,000 Kaki by Dr. Gia Pratama which describes the personality structure of the main character. The data in this research is analyzed by using content analysis technique and using literary psychology approach. The data is presented in narrative form because each data is described based on the results of the research conducted. From the results of the research, the personality structure of the main character in the novel Cinta 31,000 Kaki by Dr. Gia Pratama was found. The personality structure consists of: id, ego and superego.